31.5k views
5 votes
Lol can you help if you can

Lol can you help if you can-example-1
User Jayashri
by
4.5k points

2 Answers

4 votes

Answer:

y = (x - 12)^3

y = (x - 4)^3

Explanation:

If you look in the picture, red line is y = x^3 (the original parent equation), green line is y = (x - 4)^3, and blue line is y = (x - 12)^3

Lol can you help if you can-example-1
User Kedisha
by
5.8k points
6 votes

Answer:

y= (x - 12)^3

y= (x - 4)^3

Explanation:

Shift to the right is a horizontal shift so it needs to be with x in the parenthesis. And negative because it is to the right.

y= (x - 12)^3

y= (x - 4)^3

are the two that fit those criteria

User Micahmills
by
5.7k points